2008
DOI: 10.1177/0269215508090771
|View full text |Cite
|
Sign up to set email alerts
|

Early activation or a more protective regime after arthroscopic subacromial decompression — a description of clinical changes with two different physiotherapy treatment protocols — a prospective, randomized pilot study with a two-year follow-up

Abstract: Early activation using a comprehensive, well-defined and controlled physiotherapy protocol can be used safely after arthroscopic subacromial decompression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 38 publications
(47 reference statements)
0
6
0
Order By: Relevance
“…Noted pain reduction was similar for both groups. 12 A recent multi-centre trial concluded that a standardized physiotherapy exercise intervention results in statistically significant and clinically relevant improvement in shoulder pain and function at 12 months when compared with traditional care. 11 We have developed a telerehabilitation programme to provide outpatient rehabilitation for patients who have undergone ASD.…”
Section: Introductionmentioning
confidence: 99%
“…Noted pain reduction was similar for both groups. 12 A recent multi-centre trial concluded that a standardized physiotherapy exercise intervention results in statistically significant and clinically relevant improvement in shoulder pain and function at 12 months when compared with traditional care. 11 We have developed a telerehabilitation programme to provide outpatient rehabilitation for patients who have undergone ASD.…”
Section: Introductionmentioning
confidence: 99%
“…One of the essential components of rehabilitation programmes for patients with shoulder impingement syndrome is therapeutic exercise, which is now considered to be an effective intervention for this condition [25][26][27][28][29][30][31][32][33][34][35]. Despite the limited evidence of the effectiveness of physical means, the results suggest that, rather than the physical means used, the most important factor in functional recovery in patients with shoulder impingement syndrome is exercise [28].…”
Section: Discussionmentioning
confidence: 99%
“…Compared to these heterogeneous animal studies, prospective studies of humans provide a good level of data. Early passive exercise does not appear to be disadvantageous [ 19 ]. Both Chan et al.…”
Section: Immobilization and Arm Positioningmentioning
confidence: 99%